Penerapan Model Problem Based Learning dalam Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Reza Gunawan; Muhammad Hasan; Kasmawati Kasmawati; Jospiar AS (LaGeografia, 2023)
One of the skills that students need to have in 21st-century learning is critical thinking skills. In improving critical thinking skills, a learning model that can be used is needed, namely a problem-based learning model. For this reason, this research aims to reveal how the application of the problem-based learning model can improve students' critical thinking skills in class X at SMAN 2 Gowa. This research uses a type of classroom action research that is carried out in two learning cycles. The data collection technique used was observation with research instruments in the form of learning implementation plans, student worksheets, and observation guidelines. The research results show that the application of the problem-based learning model can improve students' critical thinking skills in class X at SMAN 2 Gowa. The implication of this research is that teachers in educational units are expected to be able to use the problem-based learning model considering it has been proven to improve student's critical thinking abilities. The application of the problem-based learning model in the future also needs to be applied at other levels, such as from elementary school to tertiary level.AbstrakSalah satu keterampilan yang perlu dimiliki peserta didik dalam pembelajaran abad-21 yakni keterampilan berpikir kritis. Dalam meningkatkan keterampilan berpikir kritis diperlukan model pembelajaran yang dapat digunakan yakni model problem based learning. Untuk itu, penelitian ini memiliki tujuan dalam mengungkap bagaimana penerapan model problem based learning dapat meningkatkan kemampuan berpikir kritis peserta didik kelas X di SMAN 2 Gowa. Penelitian ini menggunakan jenis penelitian tindakan kelas yang dilaksanakan sebanyak dua siklus pembelajaran. Teknik pengumpulan data yang digunakan yakni observasi dengan instrumen penelitian berupa rancangan pelaksanaan pembelajaran, lembar kerja peserta didik, dan pedoman observasi. Hasil penelitian menunjukkan bahwa penerapan model problem based learning dapat meningkatkan kemampuan berpikir kritis peserta didik kelas X di SMAN 2 Gowa. Implikasi penelitian ini yaitu guru di satuan pendidikan diharapkan dapat menggunakan model pembelajaran problem based learning dikarenakan terbukti dapat meningkatkan kemampuan berpikir kritis peserta didik. Penerapan model problem based learning kedepannya perlu juga diterapkan pada jenjang lain seperti mulai dari jenjang sekolah dasar hingga perguruan tinggi.